2011
DOI: 10.1111/j.1465-3362.2010.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost of privatisation versus government alcohol retailing systems: Canadian example

Abstract: Alcohol-attributable burden and associated costs will increase markedly if all Canadian provinces and territories gave up the government alcohol retailing systems.For public health and economic reasons, governments should continue to have a strong role in alcohol retailing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…As noted below, this erosion appears to be driven by customer interest in greater convenience and commercial interest in wider and more effective distribution and sale of their products. This is further supported by the research from Rehm et al [15] and Popova et al [16] focusing on Canada, and Stockwell et al [17] focusing on Sweden. These studies point to a projected substantial increase in harms if full privatisation of alcohol retailing is implemented.…”
Section: Introductionsupporting
confidence: 52%
“…As noted below, this erosion appears to be driven by customer interest in greater convenience and commercial interest in wider and more effective distribution and sale of their products. This is further supported by the research from Rehm et al [15] and Popova et al [16] focusing on Canada, and Stockwell et al [17] focusing on Sweden. These studies point to a projected substantial increase in harms if full privatisation of alcohol retailing is implemented.…”
Section: Introductionsupporting
confidence: 52%
“…Nonetheless, before turning to the second facet of epidemiological dynamics, epidemic spread, readers should note that upstream interventions directed toward alcoholic beverages and tobacco seem to be yielding much more promising results than has been the case for internationally regulated drugs. In relation to these legal drugs, not yet subject to international controls, government-directed regulation of price, taxation, and availability might be the most effective policy instruments that constrain the availability of these compounds and the prevalence of their extramedical use (for recent reviews and new contributed evidence, see Popova et al, 2011 ;Ribisl, Williams, Gizlice, & Herring, 2011 ). In addition, whether induced by government policy or action or by other means, disruption of street-level availability of internationally regulated drugs may certainly infl uence the occurrence of extramedical drug use and drug-related harms (e.g., see Bejerot, 1975 ;Brill & Hirose, 1969 ;Lenke & Olsson, 1998 ).…”
Section: Upstream Interventions With Respect To Tobacco and Alcoholmentioning
confidence: 99%
“…Research has shown that increasing the availability of alcohol is related to increased consumption and alcohol-attributable morbidity and mortality [ 17 20 ]. Further, alcohol-related harms have repercussions that can affect others in the community [ 21 ].…”
Section: Introductionmentioning
confidence: 99%